PROJECT-BASED LEARNING OF ROBOTIC SPECIALIZATION IN BACHELOR DEGREE PROGRAM - B. I. Shakhtarin; V. V. Weltishev (Научный вестник МГТУ ГА)
In the article the author imparts the experience of teaching project disciplines using medium-level computer systems beginning with lower level with the further transition to upper level systems. The results of the introduction of an experimental technique of teaching project training are given. The article considers the introduction of an experimental technique of project training in the course "The fundamentals of robotic systems automation". The project suggests applying CAD systems to develop a geometrical model of a submersible craft, which will be used in future to design project documentation as well as a control system and a simulator. The project distinction is affected with conditions of individual assignment fulfilment without using ready solutions. The project subject-matter is defined with knowledge system of future bachelor specialization in the area of robotics. The article demonstrates stage methods of training and supervision over project fulfilment with IT application according to modular approach. In practice bachelors take intense interest in theoretical and practical project-based learning if they use modern IT.